serum level of IgA, IgG, IgM, CA125, CEA, migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4) in gastric cancer after treatment : serum markers in gastric cancer - Huang, Ying; Hu, Yueming; Gu, Fengwei; Ni, Yufeng (Journal of Medical Biochemistry, 2025)
Objective: The current study was undertaken to assess the effects of the treatment on ( IgA, IgG, IgM, CA125, CEA, migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4) in patients with advanced gastric cancer. Methods: In this randomized clinical trial, 100 patients with gastric cancer were recruited after excluding 8 ineligible cases and assigned to receive either oxaliplatin (reference group) or the SOX regimen (observation group) via random number table method at a ratio of 1:1, with 50 patients in each group. The primary clinical endpoint was clinical efficacy, and secondary endpoints included immune function, tumor markers, and chemotherapy toxicities. Results: The SOX regimen was associated with significantly higher clinical efficacy versus oxaliplatin monotherapy, as indicated by the higher disease control rate and objective remission rate (P<0.05). The SOX regimen provided better immunity recovery of patients versus oxaliplatin alone, evidenced by the higher levels of immunoglobulin A (IgA), immunoglobulin G (IgG), immunoglobulin M (IgM), CD3+, CD4+ and natural killer (NK) cells and lower CD8+ levels in the observation group (P<0.05). The SOX regimen provided markedly higher anti-tumor benefits than oxaliplatin monotherapy, evinced by the significantly reduced serum concentrations of tumor markers, including cancer antigen 125 (CA125), carcinoembryonic antigen (CEA), migration inhibitory factor-related protein 14 (MRP14), stromal cell-derived factor 1 (SDF-1), fibroblast-specific protein 1 (FSP-1), and C-X-C Motif Chemokine Receptor 4 (CXCR4) (P<0.05). The SOX regimen was associated with a higher safety profile versus single oxaliplatin by reducing the occurrence of nausea and vomiting and leukopenia in patients (P<0.05). Conclusion: The SOX regimen provides a viable treatment alternative for advanced gastric cancer management with favorable clinical efficacy. It enhances immune function, reduces tumor marker concentrations and toxic side effects of chemotherapy, and offers substantial prognostic benefits.